ODPOWIEDZIALNOŚĆ ZSRR ZA NARUSZENIA PRAWA MIĘDZYNARODOWEGO W STOSUNKU DO POLSKI W LATACH 1939-1945 - Czubocha, Krzysztof (Zeszyty Prawnicze, 2017)
International Responsibility of the Soviet Union for its Illegal Actions against Poland between 1939 and 1945 Summary The author of the paper comes to a conclusion that many actions concerning Poland taken by the Soviet Union during The Second World War constituted an abuse of power. The Soviet U nion invaded Poland and illegally occupied its Eastern territories until 1945. As a result of the aggression, hundreds of thousands of Polish soldiers and citizens were killed or persecuted. At the end of The Second W orld W ar decisions concerning Poland were taken at inter-Allied conferences w ithout Poland’s participation. The Great Powers decided to deprive Poland of its Eastern territories against the will of the Polish Government-in-exile, which was legal at that time. W hat is more, Poland was not a signatory of the Jalta and Potsdam agreements. Therefore, the decisions referring to Polish Eastern border should be invalid As far as the problem of a new Polish government is concerned, it is necessary to stress that according to international law a change of a government in a particular state should take place w ithout any external interference. Nevertheless, the Soviet U nion decided to create a new government for Poland to replace the legal government-in-exile. As a consequence, the Provisional Government of National Unity was created., It consisted mostly of communists who were dependent on the Soviet Union. Many o f them were Soviet spies. They were able to gain power only as a result of the Soviet military intervention in Poland. The government did not represent Polish society and was created against its will. The Soviet U nion did not have the right to impose this sort of government on Poland. The problem of reconciliation between Poland and Russia is also approached in the paper. During the Second World War Polish state and its citizens suffered great losses. Neither the Soviet U nion nor Russia has ever assumed responsibility for the Soviet U nion’s illegal actions against Poland and its citizens between 1939 and 1945. In such circumstances any sort of reconciliation cannot take place.